Cocoa agroforestry for increasing forest connectivity in a fragmented landscape in Ghana - Asare, R.; Afari-Sefa, Victor; Osei-Owusu, Y.; Pabi, O. (Springer, 2014)
In Ghana, farmers perceive protected forestsas land banks for increasing agricultural productivity tosupport subsistence living. This has led to fragmentationof existing protected forests. Two of such reserve forestsnamely Bia Conservation Area and Krokosua HillsForest Reserve have been encroached through lumberingfor timber and area expansion of no-shade cocoaproduction systems. The purpose of this study was todevelop a multi-disciplinary strategy to increase forestconnectivity using cocoa agroforest corridors. Biophys-ical assessments involving satellite images for vegetationpatterns, and expert data from a decision support systemwere used to select suitable sites for the corridor within aGeographic Information System framework. Socio-eco-nomic assessments of the opportunity costs of alternativefarming systems to cocoa agroforestry in the delineatedcorridors show that while timber trees planted withincocoa agroforests settings would help offset the yieldlosses in cocoa shade-yield relationships compared to fullsun-production systems, the on-farm benefits of cocoaagroforestry alone are insufficient to justify the adoption.Paying farmers premium prices for cocoa and substantialoff-farm environmental and ecosystem services underagroforestry systems cantip the balance towards adoption.